Sparse random graphs: Eigenvalues and eigenvectors. Issue 1 (5th March 2012) - Tran, Linh V.; Vu, Van H.; Wang, Ke
Abstract In this paper, we prove the semi‐circular law for the eigenvalues of regular random graph Gn, d in the case d →∞, complementing a previous result of McKay for fixed d. We also obtain a upper bound on the infinity norm of eigenvectors of Erdős–Rényi random graph G(n, p), answering a question raised by Dekel–Lee–Linial. © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 2012